A MCDM-Based Meta-Heuristic Approach for U-shaped Disassembly Line Balancing Problem. Issue 1 (February 2021) - Wang, Yifeng; Xie, Yang; Ren, Yaping; Zhang, Chaoyong
Abstract: Since the rapid development of technology advancement and accelerated upgrading rate of mechanical, electrical, and electronic equipment, dealing with the recovery, recycling, and remanufacturing of end-of-life (EOL) products are of increasing importance. The disassembly line balancing problem (DLBP) aims at addressing such concern in the most efficient and effective manner. In this paper, a meta-heuristic approach involving both multi-criterion decision making (MCDM) and variable neighborhood search (VNS) is proposed to the U-shaped layout of the disassembly line. Following the MCDM method combining fuzzy set theory, grey relational analysis, and Choquet fuzzy integral, an improved VNS approach with a specially designed decoding method is utilized to balance a U-shaped line with three hierarchical objectives. Finally, computational experiments validate the effectiveness of the proposed approach.